Exploring the axion potential and axion walls in dense quark matter - Zhang, Bonan (2023)
We study the potential of the Quantum Chromodynamics axion in hot and/or dense quark matter,within a Nambu-Jona-Lasinio-like model that includes the coupling of the axion to quarks. Differently from previous studies, we implement local electrical neutrality and beta-equilibrium, which arerelevant for the description of the quark matter in the core of compact stellar objects. Firstly wecompute the eects of the chiral crossover on the axion mass and self-coupling. We and that the lowenergy properties of axion are very sensitive to the phase transition of Quantum Chromodynamics,in particular, when the bulk quark matter is close to criticality. Then, for the first time in theliterature we compute the axion potential at nite quark chemical potential and study the axiondomain walls in bulk quark matter. We and that the energy barrier between two adjacent vacuumstates decreases in the chirally restored phase: this results in lower surface tension of the walls.Finally, we comment on the possibility of production of walls in dense quark matter.